Binding and Encapsulation of Doxorubicin on Smart Pectin Hydrogels for Oral Delivery - Bosio, Valeria Elizabeth (2012)
Pectins (Pec) of 33 to 74 % esterification degree were tested with doxorubicin (Dox), a very high toxic drug widely used in cancer therapies. Pec with 35 and 55 % DE were selected because of the Dox binding higher than Pec microspheres of 35 and 55 % obtained by ionotropic gelation with Ca+2 have 88 and 66 % Dox loading capacity. Kinetic Dox release showed more than 80.0 and about 30.0 % free drug from 35 % and 55 % Pec formulations at pH 7.4, and 37 °C after 1-h incubation, respectively. Besides, Dox release decrease to 12 % in 55 % Pec microsphere formulation after 1-year storage at 4 °C. FTIR analysis of Pec–Dox complex showed hipsochromic shifts for the σC0O, δN-H and σC-C vibrational modes compared to Dox spectrum suggesting strong interaction between the drug cargo and the matrix. Rheological studies of Pec and Pec–Dox samples flow behavior exhibited a shear-thinning nature. Fifty-five percent of Pec showed higher viscosity than the viscosity for 35 % Pec in all range of temperatures analyzed, and decreased when the temperature is raised. Besides, Pec–Dox complexes have higher viscosity values than those of the corresponding Pec samples, and viscosity curves as function of shear rate for 35 % Pec–Dox are above the curves of 55 % Pec–Dox. In both cases, the results are confirming significant interaction between the cargo and the matrix, which also was established in viscoelastic dynamic analysis.